Forensic biomechanics - Kieser, Jules. (Essentials of forensic science, 2013)
"The book not only provides an in-depth examination of the field of trauma biomechanics, but also discusses the role of biomechanical principles in the analysis of blood-splatter patterning, assault and child abuse, ballistics and the investigation of the fracture of fibers and textiles"--Provided by publisher.